Magnetic resonance imaging of interaction and coalescence of two bubbles injected consecutively into an incipiently fluidized bed. (23rd November 2019) - Boyce, C.M.; Penn, A.; Lehnert, M.; Pruessmann, K.P.; Müller, C.R.
Highlights: Magnetic resonance imaging (MRI) visualizes interaction of two bubbles. Particle flow fields around two bubbles are imaged. Regimes of bubble interaction are mapped. The data provides a strong set of challenge problems for computational models. Abstract: Rapid magnetic resonance imaging (MRI) was used to visualize and quantify the interaction of two bubbles injected into an incipiently fluidized bed. The particle size, bubble sizes and the vertical and horizontal separations between bubbles were varied to understand their effects on bubble behavior. Image analysis quantified the size, shape and position of the bubbles over time. Bubbles were found to either (a) coalesce, (b) influence one another without coalescing or (c) have a collapse of a lower bubble due to influence from the upper bubble. In all cases, the lower bubbles were much more influenced in their rise by the upper bubbles than vice-versa, as lower bubbles accelerated toward the wakes of upper bubbles. Upper bubbles developed spherical cap shapes, while lower bubbles elongated vertically elongated as they rose. The experimental data provided here will serve as excellent benchmarks to challenge the assumptions made in computational and theoretical models.